Security analysis of a homomorphic signature scheme for network coding. Issue 18 (11th August 2015) - Cheng, Chi; Jiang, Tao; Liu, Yining; Zhang, Mingwu
Abstract: Recently, Liu and Wang proposed a homomorphic signature scheme for network coding, which was claimed to resist against pollution attacks. However, we show that in Liu and Wang's scheme, after several generations, the adversary is able to launch a successful forgery attack with a high probability. Therefore, Liu and Wang's scheme is not secure. After analyzing the cause of the attack, an improved scheme is given, which can combat against the proposed attack in an efficient way. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We show that in Liu and Wang's scheme, after several generations, the adversary is able to launch a successful forgery attack with a high probability. Therefore, Liu and Wang's scheme is not secure. After analyzing the cause of the attack, an improved scheme is given, which can combat against the proposed attack in an efficient way.